Formulation and Characterization of Edoxaban-Loaded Solid Lipid Nanoparticles - B. Shinde, Dipali; S. Awate, Shyam; R. Arote, Sanjay; S. Warkad, Swaraj (Journal of Neonatal Surgery, 2025)
To produce solid lipid nanoparticles of Edoxaban to increase pharmacokinetics and anticoagulant efficacy in rats. Edoxaban-loaded solid lipid nanoparticles were optimized using the central composite architecture. Particle size and %EE were dependent factors, whereas medication, lipid, and surfactant concentrations were independent variables. The optimized Edo-SLN projected particle size, %EE, and PDI values, which matched the actual values. DSC findings validated the drug's amorphous state in the optimized Edo-SLN, whereas TEM data revealed nanodispersion and spherical particle shape. Drug burst and sustained release were seen in the formulations. Pharmacokinetic studies demonstrated that optimized Edoxaban formulations had higher bioavailability than simple drug solution. Better body weight and lower fasting blood glucose were seen with optimized Edo-SLN than with standard medication suspension. Edoxaban-loaded SLN were effectively synthesized and managed anticoagulant activity well. Data suggests SLN may improve Edoxaban bioavailability for anticoagulant treatment. They lower dose frequency compared to traditional dosage forms, improving patient compliance. These may be used to reduce blood clotting in the future..